Adf-1 is a nonmodular transcription factor that contains a TAF-binding Myb-like motif. - Cutler, G.; Perry, K.M.; Tjian, R. (Molecular and Cellular Biology, 1998)
Adf-1 is an essential Drosophila melanogaster sequence-specific transactivator that binds the promoters of a diverse group of genes. We have performed a comprehensive mapping of the functional domains of Adf-1 to study the role of transactivators in the process of gene activation. Using a series of clustered point mutations and small deletions we have identified regions of Adf-1 required for DNA binding, dimerization, and activation. In contrast to most enhancer-binding factors, the Adf-1 activation regions are nonmodular and depend on an intact protein, including the Adf-1 DNA-binding domain, for activity. Like many transcriptional activators, Adf-1 contains a TFIID-binding domain that can interact with specific TAF subunits. Although TAFs are required for Adf-1-directed activation, TAF binding is not sufficient, suggesting that Adf-1 may direct multiple essential steps during activation. Interestingly, both the TAF-binding domain and the DNA-binding domain contain sequences homologous to those of the Myb family of DNA-binding domains. Thus, Adf-1 has evolved an unusual structure containing two versions of the Myb motif, one that binds DNA and one that binds proteins.